Mental health analysis on digital world with meditation using EEG - Saravanan, S.; Govindarajan, S. (International Journal of Engineering and Technology, 2018)
Internet, e-mail and other social networks like Myspace, Facebook, twitter, LinkedIn are the indispensable components in today's world. These social networking makes the human to addict into the digital world. Digital world has become the integral part of our society. Addiction to the digital world slowly develops the negative symptoms in the area of physical, physiological, emotional and psychological.Â The most affected of all is the change in Emotional behaviour of the Humans.Â Emotions plays an important role in our day today life.Â The existing research work, based on subjective self-reports shows prolonged use of Digital Media induce negative emotions for Humans.Â There are several techniques are used to extract the human emotions from brain such as Electroencephalography (EEG), functional Magnetic Resonance Imaging (fMRI), or Positron Emission Tomography (PET).Â Many of the researchers are extensively used to extract the brain waves using EEG.Â The negative emotions are controlled by human through meditation.Â In this paper, the Mind Wave device has been used to extract the EEG signal using different range of age people during they use the Digital Medias and after they perform mediation. The proposed method identify the stress level of the human while they are using social media with meditation and without meditation.Â It evidently proved that the meditation reduces the stress level of human.Â Â